Dampak Internet terhadap Perilaku Generasi Muda Islam - Mukhyar Sani (Alhadharah: Jurnal Ilmu Dakwah, 2016)
The Internet is a worldwide network between computers to communicate from one place to another in different parts of this vast world in which there are various kinds of information, both positive information, as well as negative where all the information that can be accessed via the internet. Interestingly, one communication tool that can be used by the older generation and the younger generation, even though children. Behind the great benefits, he also had something that could make a person's behavior changed from good to bad when for example he was abused by Internet users including the youth of Islam. The emergence of juvenile delinquency such as fights, and various kinds of perversity can be sourced from the misuse of the internet services. In this context, among the youth of Islam needs to be done scantlings that they "are not weak feathers and then easily catch cold."Keywords: internet, youth of Islam, criminal, communication, information, technology.Internet merupakan jaringan mendunia antar komputer untuk berkomunikasi dari satu tempat ke tempat lain di belahan dunia yang luas ini yang di dalamnya terdapat berbagai macam informasi, baik informasi positif, maupun negatif dimana semua informasi itu dapat diakses via internet. Menariknya lagi, alat komunikasi yang satu ini dapat dimanfaatkan oleh generasi tua maupun generasi muda, bahkan anak-anak sekalipun. Di balik manfaatnya yang besar, ia juga menyimpan sesuatu yang dapat membuat prilaku seseorang berubah dari baik ke tidak baik ketika umpamanya ia disalah gunakan oleh pengguna jasa internet termasuk di dalamnya generasi muda Islam. Munculnya kenakalan remaja seperti perkelahian, dan berbagai jenis perbuatan menyimpang dapat bersumber dari penyalah gunaan jasa internet itu. Dalam konteks ini dikalangan generasi muda Islam perlu dilakukan pengkuatan-pengkuatan agar mereka “tidak lemah bulu dan kemudian mudah mmasuk angin.”Kata kunci: internet, generasi muda Islam, kriminal, komunikasi, informasi, teknologi.